A Model Of The Underlying Philosophy And Criteria For Effective Implementation Of Performance Management - C. M. Whitford; W. J. Coetsee (SA Journal of Human Resource Management, 2006)
The objective of this study was to develop a model that assists organisations in implementing performance management effectively. A model describing the philosophical paradigm underpinning best practice in performance management and the criteria for effective implementation of performance management was developed. The sample used in this study was a convenience sample of 615 employees. Exploratory factor analysis revealed three reliable philosophical dimensions. Moderate correlations were found between the three dimensions and some of the implementation criteria.